Chemistry in the laboratory - Hunter, Paul W. W (Michigan State University, 2005)
Changing your class schedule, checking out and checking in your equipment, wwhat to do if you miss your laboratory class, your prelab discussions or problem sets, where and how to get assistance, how your grade will be determined, the instructors and the staff for the course ;